Obstacle avoidance and object detection for semi autopilot system of an electric car - Sakib, Md. Fahim Shahriar; Anik, Md. Faysal Ahmed; Ahmed, S.K Shahriar; Khandakar, Sahadat (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.